(1,2 ) Sp-Open Sets In Bitopological Spaces - Shareef, Hardi Ali; Natarajan, Durga Devi; Ramajeyam, Raja Rajeswari; Periannan, Thangavelu (Sulaimani Journal for Pure and Applied Sciences, 2017)
In this paper, we introduce a new type of semi-open sets in bitopological spaces called Sp-open sets, and give some of its relationship with other types of open sets in bitopological spaces. A few properties of Sp-open sets are also studied.
Keywords: semiopen sets; preclosed sets; Spopen sets